Towards a multiscale framework for modeling and improving the life cycle environmental performance of built stocks. (1st April 2022) - Stephan, André; Crawford, Robert H.; Bunster, Victor; Warren‐Myers, Georgia; Moosavi, Sareh
Abstract: Cities are complex sociotechnical systems, of which buildings and infrastructure assets (built stocks) constitute a critical part. As the main global users of primary energy and emitters of associated greenhouse gases, there is a need for the introduction of measures capable of enhancing the environmental performance of built stocks in cities and mitigating negative externalities such as pollution and greenhouse gas emissions. To date, most environmental modeling and assessment approaches are often fragmented across disciplines and limited in scope, failing to provide a comprehensive evaluation. These approaches tend to focus either on one scale relevant to a discipline (e.g., buildings, roads, parks) or particular environmental flows (e.g., energy, greenhouse emissions). Here, we present a framework aimed at overcoming many of these limitations. By combining life cycle assessment and dynamic modeling using a nested systems theory, this framework provides a more holistic and integrated approach for modeling and improving the environmental performance of built stocks and their occupants, including material stocks and flows, embodied, operational, and mobility‐related environmental flows, as well as cost, and carbon sequestration in materials and green infrastructure. This comprehensive approach enables a very detailed parametrization that supports testing different policy scenarios at a material, element, building, and neighborhood level, and across different environmental flows. We test parts of our modeling framework on a proof‐of‐concept case study neighborhood in Melbourne, Australia, demonstrating its breadth. The proposed modeling framework can enable an advanced assessment of built stocks that enhances our capacity to improve the life cycle environmental performance of cities.